Characteristic time of thermal and diffusional relaxation - Aryasova, O.V.; Khazan, Ya.M. (Геофизический журнал, 2015)
It is shown that frequently used dimensional estimate of a layer thermal relaxation time, tr, as L²/k based on the layer thickness, L, and thermal diffusivity, к, strongly overestimates tr. The correct estimate tr=L²/π²k should contain a factor of 1/π² which is of the order of 0.1.